Heidegger’s concept of Stimmung and its relevance to the practice of psychotherapy (Existential Analysis: Journal of the Society for Existential Analysis, 2013)
Two key ideas on the notion of Stimmung in Heidegger's 1929/1930 lecture course will be explored, with a view to showing that therapeutic process may be akin to the way Heidegger develops questions in metaphysics; leading to a truth that is by nature that of human existence.
Keywords: Heidegger; Stimmung; mood; feeling; What is Metaphysics; therapeutic process